Improving research quality through technical guidance on qualitative research methods - St Salmah Sharon (University of Merdeka Malang, 2023)
The quality of qualitative research conducted by Master's students and lecturers at STIE Wirabakti Makassar has been lacking due to insufficient mastery of qualitative research methods. This Community Service Activity (PKM) aims to enhance the research quality by organizing a Qualitative Research Methods workshop. The PKM involves disseminating and training in Qualitative Research Methods, with material introduction conducted online and practical training held offline. The outcomes reveal a notable improvement in participants' understanding and skills in employing qualitative research methods. The primary objective of this initiative is to address challenges in crafting theses or scientific papers by offering various research methodology choices. The participants of this service were Master's students and lecturers from STIE Wirabakti Makassar. The workshop combined offline and online sessions conducted via Zoom. The workshop incorporated material presentations and interactive question-and-answer segments to gauge participants' comprehension. The results, deduced from pre-test and post-test evaluations, indicate participants' enhanced grasp of qualitative research methodologies, especially diverse paradigms introduced by facilitators. The clear and practical material presentation, supplemented with concrete examples, contributed to the participants' comprehensive understanding. The successful implementation of this initiative is anticipated to elevate the caliber of research conducted by students and lecturers, enabling them to make informed choices regarding qualitative research methods.